Effect of epoxidation and surface modification on backing-required properties of peroxide prevulcanized natural rubber–based films. (March 2014) - Wirasate, Supa; Chokbunpiam, Chompoonuch; Thonggoom, Rattaporn; Tangboriboonrat, Pramuan
The effect of epoxidation and surface modification by acrylamide grafting on backing-required properties of peroxide prevulcanized natural rubber (PPNR)-based films was investigated. Backing-required properties including oxygen transmission rate (OTR), water vapor transmission rate (WVTR) and Young's modulus were determined. In situ epoxidation of natural rubber (NR) latex was carried out using hydrogen peroxide/formic acid system. Both NR and epoxidized natural rubber (ENR) latexes were prevulcanized by tert -butyl hydroperoxide/fructose system before film casting. In the case of surface modification, acrylamide was grafted on PPNR surface by dipping the PPNR strip treated with O2 plasma into an aqueous solution of acrylamide monomer (AAm). Epoxidation showed more pronounced effect on the backing-required properties than surface grafting. As mole percentage epoxide increased, OTR decreased by 22–35%, whereas WVTR and Young's modulus increased by 116–170% and 56–138%, respectively, depending on mole percentage epoxide. In the case of surface grafting, it was found that all OTR, WVTR and Young's modulus were slightly higher than those of unmodified films.